Absence of Charge Transfer State Enables Very Low VOC Losses in SWCNT:Fullerene Solar Cells. Issue 1 (13th November 2018) - Classen, Andrej; Einsiedler, Lukas; Heumueller, Thomas; Graf, Arko; Brohmann, Maximilian; Berger, Felix; Kahmann, Simon; Richter, Moses; Matt, Gebhard J.; Forberich, Karen; Zaumseil, Jana; Brabec, Christoph J.
Abstract: Current state‐of‐the‐art organic solar cells (OSCs) still suffer from high losses of open‐circuit voltage ( V OC ). Conventional polymer:fullerene solar cells usually exhibit bandgap to V OC losses greater than 0.8 V. Here a detailed investigation of V OC is presented for solution‐processed OSCs based on (6, 5) single‐walled carbon nanotube (SWCNT): [6, 6]‐phenyl‐C71 ‐butyric acid methyl ester active layers. Considering the very small optical bandgap of only 1.22 eV of (6, 5) SWCNTs, a high V OC of 0.59 V leading to a low E gap / q − V OC = 0.63 V loss is observed. The low voltage losses are partly due to the lack of a measurable charge transfer state and partly due to the narrow absorption edge of SWCNTs. Consequently, V OC losses attributed to a broadening of the band edge are very small, resulting in V OC, SQ − V OC, rad = 0.12 V. Interestingly, this loss is mainly caused by minor amounts of SWCNTs with smaller bandgaps as well as (6, 5) SWCNT trions, all of which are experimentally well resolved employing Fourier transform photocurrent spectroscopy. In addition, the low losses due to band edge broadening, a very low voltage loss are also found due to nonradiative recombination, Δ V OC, nonrad = 0.26 V, which is exceptional for fullerene‐based OSCs. Abstract : The absence of a charge transfer (CT) state is found in the (6, 5) single‐walled carbon nanotube:PC70 BM system and a detailed analysis of the open‐circuit voltage ( V OC ) is reported. The analysis reveals that the lack of the CT state enables very small radiative as well as nonradiative V OC losses for an organic cell, despite the ultranarrow bandgap of this system.